2014
DOI: 10.1016/j.taap.2014.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Oral intake of hydrogen-rich water ameliorated chlorpyrifos-induced neurotoxicity in rats

Abstract: Chronic exposure to low-levels of organophosphate (OP) compounds, such as chlorpyrifos (CPF), induces oxidative stress and could be related to neurological disorders. Hydrogen has been identified as a novel antioxidant which could selectively scavenge hydroxyl radicals. We explore whether intake of hydrogen-rich water (HRW) can protect Wistar rats from CPF-induced neurotoxicity. Rats were gavaged daily with 6.75mg/kg body weight (1/20 LD50) of CPF and given HRW by oral intake. Nissl staining and electron micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 50 publications
0
26
0
Order By: Relevance
“…Recently, clinical trials have also proven the benefits of HRW in attenuating oxidative stress and inflammation in patients [17,18]. Particularly, oral intake of HRW displays anti-neurotoxicity effects by regulating the oxidant and antioxidant status of rats [19]. In addition, Li et al found that HRW plays a protective role in a rat model of Aβ-induced neural inflammation and learning-memory deficits [20].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, clinical trials have also proven the benefits of HRW in attenuating oxidative stress and inflammation in patients [17,18]. Particularly, oral intake of HRW displays anti-neurotoxicity effects by regulating the oxidant and antioxidant status of rats [19]. In addition, Li et al found that HRW plays a protective role in a rat model of Aβ-induced neural inflammation and learning-memory deficits [20].…”
Section: Introductionmentioning
confidence: 99%
“…In the screening platform, the third compound (C3) of the seventh pool (P7), thereby named P7C3, was discovered to augment postnatal hippocampal neurogenesis by protecting young hippocampal neurons from dying, without affecting their rate of proliferation, and was also shown to mitigate cognitive decline in terminally aging rats (11). Subsequent medicinal chemistry efforts led to more potent variations of the original P7C3 molecule (1214) and also generated bioactive probes that facilitated the discovery that P7C3 molecules enhance flux of nicotinamide adenine dinucleotide (NAD) in mammalian cells (15). Treatment with P7C3 has recently been shown to indirectly mitigate other critical cell death signaling events as well (16).…”
mentioning
confidence: 99%
“…Recently, Watanabe et al demonstrated that radiation-induced rat skin injury can potentially be alleviated by the pre-inhalation of hydrogen-containing gas [12]. Drinking HRW has been reported to have preventative or/and therapeutic effects in many stress-induced organ injuries [13, 14]. …”
Section: Introductionmentioning
confidence: 99%